Advanced echocardiography with left atrial strain and indexed left atrial 3D volume for predicting underlying atrial fibrillation after cryptogenic stroke. (3rd October 2022) - Vera Sainz, A; Cecconi, A; Ximenez Carrillo, A; Ramos, C; Martinez Vives, P; Lopez Melgar, B; Sanz Garcia, A; Ortega, G; Montes, A; Aguirre, C; Vivancos, J; Alfonso, F; et al.
Abstract: Introduction: Cryptogenic stroke (CS) represents one-third of ischemic strokes. Atrial fibrillation (AF) can be detected in up to 30% of CS. Therefore, there is a clinical need for predicting AF to guide the optimal secondary prevention strategy. The evidence about the role of advanced echocardiography, including left atrial 3D index volume and left atrial strain (LAS) techniques, to predict underlying AF in this setting is lacking. Methods: From April 2019 to November 2021 seventy-eight consecutive patients with ischemic stroke or transient ischemic attack with ABCD2 scale ≥4 of unknown etiology were prospectively recruited. Echocardiography was performed during admission. All patients underwent 15 days wearable Holter monitoring. The primary outcome measure was AF detection during follow-up. Results: Twenty -two patients (28%) developed AF. Patients in the AF group were older (81±6.3 vs 76.5±7.8 years; p=0.012). Left atrial (LA) diastolic indexed volume was higher in AF group (37.2±12.8 vs 29.7±11 ml/m 2 p=0.01). 3D LA indexed volume were also higher in patients with AF (41.4±14 vs 32.2±10 ml/m 2 p=0.009). LAS reservoir, LAS conduct and LAS contraction (LASct) were significantly lower in patients with AF (19±5.6 vs 32±10.3%; 9±4.5 vs 15±7.6; 10±5.3 vs 17±6.4, respectively, all p<0.001). On multivariate analysis LASct <13.5% and LA 3D indexed volume >44.5 ml/m 2 were independent predictors of AF (OR 10.9 [95% CI 1.09–108.2], p=0.042) (Table 1, Figure 1) Conclusion: LASct <13.5% and LA 3D indexed volume >44.5 ml/m 2 are independent predictors of underlying AF in patients with CS. Our results demonstrate the usefulness of advanced echocardiography in this challenging clinical setting. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Spanish Society of Cardiology